Exploration activities in Bangladesh Gas - Al Wahid, Adnan; Rawshan, Nadia (BRAC University, 2010)
Bangladesh, which constitutes one of the largest deltas of the world, has proved its hydrocarbon potentiality through discovery of 22 gas fields during the course of drilling only 65 wells over a period of last 90 sporadic years of exploration. Exploration activities in Bangladesh are divided in three phases. Phase I (1910-1933), Phase II (1951-1971) and Phase III (1971-2004). The method and intensity of exploration activity changed with the change in regime, technology, economic system and political environment. In phase-III, the Bangladesh Government undertook different strategies under different long-term plans. International Oil Companies (IOCs) have joined in exploration activities under PSC from 1993.